Enhancing Ecological Awareness through Innovative Green Sociology Teaching Approaches - Ghufronudin, Ghufronudin; Liestyasari, Siany Indria; Budiati, Atik Catur; Parahita, Bagas Narendra; Astutik, Dwi; Siregar, Riadi Syafutra (Jurnal Pendidikan Progresif, 2024)
Enhancing Ecological Awareness through Innovative Green Sociology Teaching Approaches. Objective: This study looks at how ecological intelligence and green sociology in sociology instruction. The goal of the study is to pinpoint practical methods for fostering ecological literacy, which entails becoming aware of environmental systems and taking sustainable action. The objective is to encourage sustainable thinking and behavior in students by fusing the theoretical basis of Green Sociology with effective teaching strategies. Methods: Using a literature review methodology, academic sources on sustainability in education, ecological intelligence, and green sociology were examined. The study used thematic analysis to highlight pertinent teaching practices by synthesizing findings from reputable papers, books, and scholarly publications. The study focused on techniques such as case study discussions, simulations, and project-based learning (PBL) as means of successfully integrating environmental issues into sociology courses. Result and Discussion: The results show that Green Sociology offers a thorough framework for comprehending the intricate relationships that exist between ecosystems and civilization. Students' critical thinking and ecological intelligence are improved by using techniques like simulations, problem-based learning, and community-focused projects. Students can actively participate in sustainable practices and contextualize global issues by incorporating local environmental issues into educational activities. Conclussion: Green sociology serves as an important link between sociology education and environmental sustainability. Using methods such as case studies, simulations, and PBL, educators can greatly improve students' ecological literacy. This method not only broadens their theoretical understanding, but also provides them with the skills and drive to implement sustainable activities, resulting in a more environmentally conscious generation.  Keywords: ecological intelligence, green sociology, sociology learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024139